Management of Artificial Intelligence (AI) Integration in Islamic Religious Education: Innovation Strategies and Strengthening Spiritual Values in Madrasah - Aldi Prasetiyo; Moh. Harun Al Rosid (Yayasan Darusssalam Bengkulu, 2026)
This study examines the management of artificial intelligence (AI) integration in Islamic Religious Education at madrasahs, focusing on innovation strategies and the strengthening of spiritual values. The study employed a qualitative descriptive approach at MA Al-Amiriyyah Blokagung Banyuwangi. Data were collected through interviews, observation, and documentation involving the headmaster, teachers, students, and pesantren administrators. Data analysis used the interactive model of Miles and Huberman, while data validity was ensured through triangulation and member checking. The findings reveal the formation of an integrative AI-spiritual management model in which AI functions as a supportive educational tool while remaining grounded in Islamic values and ethics. The study also identifies the transformation of teachers into “spiritual-tech educators” who combine digital competence with spiritual responsibility. Furthermore, AI demonstrates a dual impact by improving students’ cognitive understanding and learning engagement while also presenting challenges to spiritual reflection if not properly guided through value-based and ethical educational management strategies.